КАРАКАЛПАКСКИЙ ДАСТАН «ЕДИГЕ» С ТОЧКИ ЗРЕНИЯ ЗАРУБЕЖНЫХ УЧЁНЫХ: НЕКОТОРЫЕ ВОПРОСЫ ПРОБЛЕМЫ СБОРА, ПУБЛИКАЦИИ И ИЗУЧЕНИЯ - Алламбергенова, Г.К. (SCIENCE and SOCIETY, 2020)
The article deals with the investigation and publication of the Karakalpak folk epos «Edige» by the scholars of foreign countries and the issues of creation, genesis and typological genre peculiarities of the epos. On the basis of study of national versions by the method of typological comparison, the author comes to the conclusion that all the national versions have the same national spiritual-aesthetic source. The versions appeared at different periods of time and are connected with social-political and social-economical conditions. In the result of it there appeared the Karakalpak, Nogai, Kazakh, Tatar and Bashkir versions. According to the opinion of scholars, the Karakalpak version is considered to be the most perfect national version in the artistic form and it is close to the architype.